Peculiarities of the course of demodicosis in domestic animals in a megalopolis in the east of Ukraine - A. Paliy; O. Pavlichenko; S. Kasianenko; L. Kovalenko; A. Stockiy; O. Stotska (Regulatory Mechanisms in Biosystems, 2023)
Demodicosis in domestic animals occupies a leading place among dermatological diseases. It has considerable epizootological and social significance. Peculiarities of the manifestation of demodicosis in dogs and cats were studied in the city of Kharkiv during 2017–2021. Doberman Pinscher, mestizo, German Shepherd, Rottweiler, Staffordshire Terrier, and outbred animals were the most commonly affected by demodicosis, accounting for 61.6% of the total number of patients. The lowest number of animals with demodicosis was registered in such breeds as Dalmatian, Great Dane, Caucasian Shepherd, Collie, Labrador, Husky, Pekingese, and Chow Chow with a total number of 4.6%. Demodicosis is most common in Persian white, European tiger, and Siamese colour point cats, accounting for 57.3%. Norwegian forest, Russian blue, and Oriental shorthair cats are rarely affected by demodicosis, accounting for 13.5% of all animals. Demodicosis most often affects animals aged from 2 months to 3 years in winter, and in summer and autumn, the incidence is lowest. Peculiarities of sexual predisposition of animals to demodicosis infection have not been established. The microbes affecting the skin of animals are transmitted by mites Demodex spp. and are represented by Staphylococcus spp., Streptococcus spp., Enterobacter spp., Enterococcus spp., Micrococcus spp., Alternaria alternata, Aspergillus niger, Candida spp., Rhizopus nigricans, Penicillum spp., Malassezia spp., Microsporum canis. Staphylococcus spp. and Streptococcus spp. occupy the largest percentage of the total number of isolated microorganisms – 74.7%, and Micrococcus spp. occupy the lowest percentage of isolated microorganisms (6.2%). Staphylococcal susceptibility to nine tetracycline drugs has shown a high level of resistance. The most effective antimicrobial agent for isolated cultures of staphylococci is amoxicillin in combination with clavulanic acid (89.7%) and vancomycin (100.0%). The objective of further research is to develop effective schemes for the prevention and treatment of pets with demodicosis.